A communication law feared and discussed by the press: The case of ecuador - Yaguache Quichimbo, J. (2017)
Much academic research is focused on the current situation of Ecuador with regard to journalism and media management after the application of the Communications Law. The media lynching and the subsequent liability, censorship, and policies to the professional practice, are the main topics of discussion. Grievances, complaints and the closure of media have been the trends over the past two years. In addition to this situation, in December 2015, the Telecommunications Law was reformed, including the possibility for Internet users and social networks to be punished. The research analyzes the criteria of the promoters of media companies according to national, regional, and local study cases, compared to the regulatory processes running on Ecuador, which are altering the journalistic routines in traditional and digital editions. © Springer International Publishing Switzerland 2017.